(untitled) (Journal of Fatima Jinnah Medical University, 2018)
Objectives: To identify factors responsible for delay in presentation of carcinoma of breast Patients and Methods: A cross-sectional study was conducted at Surgical Unit I Sir Ganga Ram Hospital, Lahore from January 2009 to April 2014. A total of 200 females were included. Diagnosis of breast carcinoma was based on histopathology. Factors such as lack of awareness about disease, lack of medical facility, management from quacks, hakeems and homeopathic medicines and spiritual healers were collected employing a short structured proforma. Results: Lack of awareness was responsible for 69.5% of cases. Next common was lack of health facility responsible for 20.5% of cases. Management of quacks, Hakeems and homeopathic medicines was responsible for 6.5% of cases and Spiritual Healing was responsible for 3.5% of cases Conclusion: It is strongly recommended that in Pakistan awareness about the disease should be increased and there is also a dire need of setting up medical facilities in Pakistan both in cities and also in remote areas so that carcinoma of breast should be detected early and be managed accordingly without any delay because these factors are preventable.